Evaluating an implementation of the Australian National Guidelines for the On-Screen Display of Discharge Summaries. - Mahera, Masarrat; Rodda, Hamish; Monypenny, Nick; Wembridge, Paul (Australian Health Review, 2023)
Objective. The objective of this study was to evaluate changes in the inclusion of pertinent information on electronic discharge summaries (eDS) after implementation of a revised template and electronic medical record (EMR) workflow. Methods. A retrospective medical record audit of eDS at three metropolitan hospitals was undertaken for adult inpatient encounters in June 2021 (pre-intervention, n = 100) and June 2022 (post-intervention, n = 100). The eDS were evaluated against 16 components listed in the Australian National Guidelines for the OnScreen Display of Discharge Summaries. Nine components were further broken down to between two and 11 sub-components. Sub-analysis compared a hospital with full EMR to pooled results from hospitals with hybrid EMRs. Components and sub-components were evaluated for inclusion only; accuracy or relevance of the information was not assessed. Results. Inclusion of three out of 16 components (presentation details: 47% vs 62%, problems and diagnosis: 61% vs 86% and recipient details: 82% vs 93%) and eight out of 36 sub-components (discharge destination, principal diagnosis, history of presenting complaint, infection risk, pressure injury, screening and/or diagnosis of delirium and GP phone number and address) was higher in the postintervention group (all P < 0.05). Reduced eDS information inclusion in the post-intervention group was observed for discharge date and falls risk only (both P < 0.05). Reporting of falls history decreased at the hospital with full EMR (71% vs 20% P < 0.001) but not at hospitals utilising hybrid EMRs (24% vs 30% P = 0.5). Conclusion. The intervention was associated with improved inclusion of pertinent information as described in the Australian National Guidelines for the On-Screen Display of Discharge Summaries.